CARTOON MOVIE AS A MEDIA TO PROMOTE SPEAKING SKILL - Basion Salman; Fauziah Fauziah; Jamaliah Jamaliah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2021)
This research reports on a case study of cartoon movie as a media to promote speaking skill at a senior high school in Sigli, Aceh. This study is an attempt to response the issue in preliminary study in which teachers did not know how to provide a creative and interesting teaching media for speaking. Considering that practicing speaking should be interesting and enjoyable, the researcher assumed that cartoon movie might contribute to students’ speaking development. Besides having potential to encourage thinking processes and discussion skills, cartoons engage the attention of the learners and present information in a non-threatening atmosphere. Two non-participant observers and 20 second-grade students of Senior High School were participated in this qualitative research design, embracing characteristics of a case study. The data were obtained from different resources, classroom observation, video recording, document, and test. The research aim was to investigate how the teacher employed cartoon movie as a teaching media to develop students’ speaking skill. The findings revealed that students motivated to take part in the classroom activities, enjoyed and felt confident to speak English, indicating that the teaching speaking through cartoon movie was successful. Keywords: Media to Promote Speaking Skill, Cartoon Movie, Teaching Speaking for EFL Students